Identification of Diversity of Medicinal Plants in Bukit Mayana Forest Area, Kuningan Regency - Agus Yadi Ismail; Sukron Aminudin; Ilham Adhya; Ai Nurlaila; Nurdin (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2023)
Bukit Mayana Forest Area is a forest area in Kuningan Regency with an area of ±43 ha with a diversity of medicinal plant species that have not been fully identified. The purpose of this study was to identify the diversity of medicinal plants in the Bukit Mayana Forest Area, Kuningan Regency. The method used is a single-plot method that is placed by purposive sampling with a size of 100 x 80 meters which is divided into sub-plots with a total of 20 plots. The data obtained are then analyzed using the important value index (INP), species diversity index (H'), species richness index (R'). The results showed that medicinal plants were found in 34 types from 23 families. The highest important value index (INP) at the tree, pole, and stake levels is Ficus fistulosa with index values of 38.16%, 91.13%, and 64.68% and seedling levels are Coffea with an index value of 15.26%. The species diversity index (H') is medium with values of 1 < H' > 3 and the species wealth index is low with R' < 3.5.